Research on the informal urban space and the methods of urban design: Based on two Chinese handscrolls in Qing Dynasty - Li Keran; Lin Yan; Xie Yuhu (Lodz University of Technology Press, 2023)
Informal space is an important part of urban vitality, which have a close relationship with figures, behaviours, and formal space. These seemingly contradictory elements can be found in some historical paintings. As the outstanding examples of the ‘genre painting’ in Qing Dynasty in China, 12 paintings of Emperor Qianlong’s Southern Trip of Inspection not only contain kinds of informality about everyday urbanism, but also show the coexistence and equilibrium between the informal and formal space. Taking the second and sixth rolls as an example, this paper analysed the image structure and spatial distribution of elements, behaviour-oriented correlation and composition of active fragments, and street interface construction and corner space from three scales of painting, fragment and scene respectively. Based on the specifications on transformation of logic, enlightenment to contemporary urban design was discussed in three aspects. Through the quantitative analysis, two pairs of very closely correlated variables were obtained and the correlations have been proven to be bidirectional anisotropy, which can support related urban design in the future. This research has developed a framework to analyse Chinese ancient paintings depicted under mixed influence of formality and informality, and explored the approaches about transformation from historical scenario to urban design.
Keywords: informal space; urban design; historical scenario; Emperor Qianlong’s Southern Trip of Inspection; przestrzeń nieformalna; urbanistyka; scenariusz historyczny; południowa podróż inspekcyjna cesarza Qianlonga